Raforkumarkaðir - og mögulegur útflutningur raforku - Margrét Ormslev Ásgeirsdóttir 1981- (2011)
For the most part, fossil fuels, mainly coal and natural gas, fuel the power generators of the world. On account of concerns over global warming and depleting reserves of fossil fuels, power generation has become a focus of reforms. Export via sea cable has been under consideration for decades. However, in the last 10 to 15 years, premises for this project have changed due to outside factors such as rising power prices, increased demand for “green power”, foreseeable decommissioning of coal and nuclear power plants in Europe, and technical progress in the field of sea cables. Domestic factors such as the commissioning of the 690 MW power plant at Karahnjukar have also had an effect, and as a consequence, the sea cable project is again up for discussion. The purpose of this study is to facilitate understanding of discussions about power and power markets with possible export of power from Iceland via sea cable as a focus point. By connecting to another power market where the price is much higher, the price of power in Iceland will rise as well. The profits made by power generators should be shared most obviously through dividends and taxes. Another way is to auction rights to utilise domestic energy resources. Overall, exporting power via sea cable is a good option given that power can be sold at a high enough price and policy makers need to start moulding a framework around the ownership, operations and division of profits. An additional result of this thesis is that to identify the best market to export to, a much more detailed analysis needs to be done identifying power generation prices, including whole market area (not only connected country) as well as studying how much, what kind and when Iceland would be exporting/importing power. Ekki er heimilt að vista eða afrita nema með leyfi höfundar.